2004
DOI: 10.1111/j.1365-3059.2004.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental conditions influencing Sclerotinia sclerotiorum infection and disease development in lettuce

Abstract: The environmental factors that influence infection of lettuce by ascospores of Sclerotinia sclerotiorum, and subsequent disease development, were investigated in controlled environment and field conditions. When lettuce plants were inoculated with a suspension of ascospores in water or with dry ascospores and exposed to a range of wetness durations or relative humidities at different temperatures, all plants developed disease but there was no relationship between leaf wetness duration or humidity and percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 17 publications
0
38
0
4
Order By: Relevance
“…Ascospore germination on lettuce leaves was optimum at 15–25°C and the rate of Sclerotinia disease development was greatest at 16–27°C [18]. However, we could not establish a relationship between leaf wetness period, or duration of different RH levels (up to 6 d), and disease levels.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Ascospore germination on lettuce leaves was optimum at 15–25°C and the rate of Sclerotinia disease development was greatest at 16–27°C [18]. However, we could not establish a relationship between leaf wetness period, or duration of different RH levels (up to 6 d), and disease levels.…”
Section: Introductionmentioning
confidence: 74%
“…The mean rate of spore germination was calculated from the data collected by Young et al, [18] (Table 1) under conditions of continuous leaf wetness and fitted using the temperature response function of Yan and Hunt [23]. The percentage rate of germination (h −1 ) was calculated as:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Imolehin et al (5) showed that sclerotia of S. minor germinated and exhibited mycelial growth at temperatures ranging from 6 to 30 o C with optimum growth at 18 o C and infection of lettuce plants occurred at temperatures ranging from 6 to 24 o C. For S. sclerotiorum, Young et al (14) verified that ascospores could cause bottom rot in lettuce at temperatures ranging from 8 to 27 o C, but the disease occurred more rapidly and was more severe at temperatures ranging from 16 to 27 o C, peaking at 22 o C.…”
Section: Discussionmentioning
confidence: 99%